2001
DOI: 10.1103/physrevd.64.013007
|View full text |Cite
|
Sign up to set email alerts
|

Higgs boson mass effects in the processμR(L)+μR(L)

Abstract: The process R(L) ϩ R(L) Ϫ →W L ϩ W L Ϫ is studied with a view to discern the Higgs boson mass effects. The helicity amplitudes are evaluated retaining muon mass terms and cancellation of possible bad high energy behavior is discussed. The results are examined in the context of the equivalence theorem. The Higgs boson mass effects in the differential cross section (d/d cos ), total cross section ͑͒, and forward-backward asymmetry (A FB ) are presented for two cases: ͑i͒ m H Ͻ2m W and ͑ii͒ m H Ͼ2m W . Near the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…46 Although FFA I is the commercial form of FFA, FFA III has been chosen as the desired polymorphic form for this study, as it represents the majority of commercial drug products where the APIs are formulated in the thermodynamically most stable polymorph at ambient conditions. 29,47 Physical mixtures (10 wt % to 80 wt %) of FFA III in PEG 4000, 10 000, and 20 000, respectively, were analyzed by PXRD to confirm that the energy input of the sample preparation and storage conditions had no adverse effect on the desired polymorphic form (FFA III) before any experiments were performed (Supporting Information). 26,27 It was concluded that within the detection limits of the PXRD employed, no traceable transformation had occurred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Although FFA I is the commercial form of FFA, FFA III has been chosen as the desired polymorphic form for this study, as it represents the majority of commercial drug products where the APIs are formulated in the thermodynamically most stable polymorph at ambient conditions. 29,47 Physical mixtures (10 wt % to 80 wt %) of FFA III in PEG 4000, 10 000, and 20 000, respectively, were analyzed by PXRD to confirm that the energy input of the sample preparation and storage conditions had no adverse effect on the desired polymorphic form (FFA III) before any experiments were performed (Supporting Information). 26,27 It was concluded that within the detection limits of the PXRD employed, no traceable transformation had occurred.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Polymorphism is estimated to occur in up to 80% of molecules that display pharmaceutical applications, 27,28 affecting properties of the solid state (stability, solubility, dissolution rate, and bioavailability), and therefore, the quality and efficacy of the final drug product. 24,26,27,[29][30][31][32] The unsubstantiated notion that undesired polymorphic phase transformations might occur during HME limits the application of this technique to produce crystalline solid dispersions for a narrow set of APIs that are both thermally stable and monomorphic (∼20%). 27,28 However, taking into consideration other industrial processes, this sentiment might be founded on insufficient knowledge of the thermodynamic and kinetic boundaries, in other words, the design space of a particular HME process.…”
Section: Introductionmentioning
confidence: 99%